Diarrhea with deficiency kidney-yang syndrome caused by adenine combined with Folium senna was associated with gut mucosal microbiota - Zhu, Jiayuan; Li, Xiaoya; Deng, Na; Peng, Xinxin; Tan, Zhoujin (Frontiers in Microbiology, 2022)
The present study aims to study and analyze the characteristics of gut mucosal microbiota in diarrhea mice with deficiency kidney-yang syndrome. Ten male mice were randomly divided into the control group and the model group. Diarrhea mice model with deficiency kidney-yang syndrome was established by adenine combined with Folium sennae. The kidney structure was observed by hematoxylin-eosin (HE) staining. Serum Na+-K+-ATP-ase and Ca2+-Mg2+-ATP-ase were detected by enzyme-linked immunosorbent assay (ELISA). The characteristics of gut mucosal microbiota were analyzed by performing third-generation high-throughput sequencing. The results showed that the model mice exhibit obvious structural damage to the kidney. Serum Na+-K+-ATP-ase and Ca2+-Mg2+-ATP-ase levels showed a decreased trend in the model group. The diversity and community structure of the gut mucosal microbiota improved in the model group. Dominant bacteria like Candidatus Arthromitus, Muribaculum, and Lactobacillus reuteri varied significantly at different taxonomic levels. The characteristic bacteria like Bacteroides, Erysipelatoclostridium, Anaerotignum, Akkermansia muciniphila, Clostridium cocleatum, Bacteroides vulgatus, and Bacteroides sartorii were enriched in the model group. A correlation analysis described that Erysipelatoclostridium was positively correlated with Na+-K+-ATP-ase and Ca2+-Mg2+-ATP-ase levels, while Anaerotignum exhibited an opposite trend. Together, adenine combined with Folium sennae damaged the structure of the kidney, affected energy metabolism, and caused disorders of gut mucosal microbiota in mice. Bacteroides, Erysipelatoclostridium, and Anaerotignum showed significant inhibition or promotion effects on energy metabolism. Besides, Akkermansia muciniphila, Clostridium cocleatum, Bacteroides vulgatus, and Bacteroides sartorii might be the characteristic species of gut mucosal microbiota responsible for causing diarrhea with deficiency kidney-yang syndrome.